2016
DOI: 10.1007/s12350-015-0223-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of extracardiac incidental findings on attenuation correction cardiac computed tomography

Abstract: This study shows that incidental findings are common and were associated with all-cause and cancer-specific mortality but only the later remained statistically significant after multivariable adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…24 Conversely, the detrimental impact of incidental findings on clinical outcome has been documented by a recent study that retrospectively identified 135 patients (12%) with incidental findings in CTAC. 25 Although these findings did not significantly increase all-cause mortality, they were associated with a significantly higher cancer-specific mortality-indicating that patients with incidental findings may more often end up with lethal cancer. Nonetheless, it is not self-evident that the detection of an incidental finding triggering instant work-up and appropriate treatment will prolong survival.…”
Section: See Related Article Pp 1574-1583mentioning
confidence: 92%
See 1 more Smart Citation
“…24 Conversely, the detrimental impact of incidental findings on clinical outcome has been documented by a recent study that retrospectively identified 135 patients (12%) with incidental findings in CTAC. 25 Although these findings did not significantly increase all-cause mortality, they were associated with a significantly higher cancer-specific mortality-indicating that patients with incidental findings may more often end up with lethal cancer. Nonetheless, it is not self-evident that the detection of an incidental finding triggering instant work-up and appropriate treatment will prolong survival.…”
Section: See Related Article Pp 1574-1583mentioning
confidence: 92%
“…Zadro et al scanned with a slice thickness of 2.5 mm during inspiration breath-hold, Qureshi et al used a 8-slice non-gated CT with a slice thickness of 3.75 mm during free breathing, 25 and the initially reported high variance of the positive predictive value regarding extracardiac findings might reflect different scan parameters such as singleslice CT vs. 16-slice CT and an acquired slice thickness of 10 mm during free breathing vs 1.5 mm during breath-hold in the four centres of the study by Coward et al 18 Due to technical refinements, acquisition parameters have continuously improved. Meanwhile, even 64-slice CT is used during inspirational breath-hold to acquire CTAC.…”
Section: See Related Article Pp 1574-1583mentioning
confidence: 99%
“…The ACC with representation and endorsement from the American Society of Nuclear Cardiology (ASNC), Society for Cardiovascular Angiography and Interventions (SCAI), Society of Atherosclerosis Imaging and Prevention (SAIP), and Society of Cardiovascular Computed Tomography (SCCT) has published training requirements for fellows-in-training and physicians in practice in Cardiovascular CT. 27,28 The American College of Radiology also has practice guideline for the performance and interpretation of cardiac CT. 29 In the current issue of the journal, Qureshi et al discuss the prevalence, prognosis, and resource utilization of extracardiac IFs on CTAC SPECT myocardial perfusion imaging. 30 They note that IFs are common (12% prevalence in their cohort) and were associated with higher all-cause and cancer-specific mortality in univariate analysis but only the latter remained statistically significant after multivariable adjustment. Another study involving CCTA did not identify extracardiac IFs as a predictor of noncardiac or cancer death.…”
mentioning
confidence: 92%
“…4 In the study by Qureshi et al the observed higher cancerspecific mortality may be due to patient selection, as almost 1/3 of their study population was African American. 30 An additional reason for the differences in IFs prevalence (12% vs 41.5%) and mortality outcomes may be related to the differences in CT parameters and resulting image quality between studies. The parameters of the 120 kVp, 20-40 mA, free breathing, and noncontrast-enhanced CTAC used by Qureshi et al 30 are quite different from the 120 kVp, 400-800 mA, gantry rotation time of 350 ms, individualized pitch, breath hold, and contrast-enhanced CCTA described by MacHaalany et al 4 As noted previously, the low-dose CTAC images are not of diagnostic quality when compared to standard-dose CT. 23 Simply put the limitations from the lower image quality CTAC would be able to identify the more obvious, larger and advanced extracardiac tumors/disease findings and potentially miss the smaller, earlier stage and possibly innocuous findings resulting in the lower prevalence and higher cancerspecific mortality as observed by Qureshi et al 30 Additional studies are needed to confirm their observations and further understand the prognostic implications of the identification of extracardiac IFs.…”
mentioning
confidence: 99%
“…Similarly, incidental findings can be seen in lowdose CT performed for attenuation correction (CTAC) during nuclear imaging, Qureshi and colleagues showed that incidental findings were common on CTAC (135 clinically significant findings in 1139 patients, 12%) and associated with cancer-specific mortality after adjustment. 12 Similarly, in a study of 1506 patients who underwent CT attenuation-corrected SPECT, 830 (55.1%) and 212 (14.1%) patients had minor and major extra-cardiac findings, respectively. Among patients with major extra-cardiac findings, the abnormality was previously unknown in 113 (53.3%) patients.…”
mentioning
confidence: 96%